Landvinning : scenarier för efterbehandling och gestaltning av Aitikgruvan, Gällivare - Fogelqvist, Simon (SLU/Dept. of Urban and Rural Development, 2008)
Open pit mining creates huge amounts of tailings and waste rock deposits. Due to it's content of sulphide minerals, predominantly pyrite (FeS2), there is a risk of oxidation and formation of acid water containing heavy metals, known as Acid Rock Drainage (ARD). To prevent the process of oxidation, the tailings and waste rock have to be reclaimed. The most commonly used methods of reclamation are a coverage of water or soil. Mining also results in a large-scale interference in the landscape that will make an eternal change of its appearance. The way the waste rock is deposited can influence the spread, elevation, and the ultimate shape. The design of the deposits makes a difference for their future appearance. The landscape design process is always a choice of contrast or interplay between the landscape and the object. A large-scale interference as a mine will contrast by differences in shape, scale, lines, colour and texture. This degree thesis makes a brief overview of the characteristics of the deposits from sulphide mines and the possible methods for reclamation of Boliden's Aitik mine, but the main purpose of this work is to give a proposal for the landscaping of the future mine area after the mining activity has ended. At the same time it's important to make a design that is long-term stable, accordingly taking the suggested methods of reclamation as a starting point. At the moment the ore is calculated to last until 2025. On the basis of the rate of production of 36 Mton per year the amounts of waste rock and tailings that will be produced during this time is known. There is a permission to deposit the waste to certain elevations. The Boliden mining company has presented a landscape plan that has won legal approval by the Environmental court. The plan indicates the levels that the waste rock deposits and the tailings dams will reach, but it doesn't reveal what shape they will adopt. The consequence of the present landscape plan will be that the deposits get a flat, horizontal shape with the crest at the ...